Strategic role players of important antimicrobial-resistant pathogens - Mujawar, Shama *; Abdella, B. *; Lahiri, Chandrajit * (IntechOpen, 2020)
Over the years, tireless efforts of the concerned scientists have produced various new therapeutics and methods for the treatment of bacterial infections. However, despite the vast regimen of modern antibiotics being corroborated, the diseases caused by the Gram-positive and -negative pathogens has become untreatable, mainly due to the constantly evolving threat of antimicrobial resistance (AMR), thereby leading to huge morbidity and mortality. Moreover, shortage of efficient therapies, lack of successful prevention strategies and availability of only a few effective antibiotics urgently necessitated the development of novel therapeutics and alternative antimicrobial treatments. These developments have been based on the molecular mechanisms of resistance posed by the pathogens during their interactions with the host. Herein, we collate four essential bacterial components like chaperones, efflux pumps, two-component systems and biofilms which can present challenges for the most coveted control of infection. Essentially, we discuss the current knowledge status of these components to provide insight into the complex regulation of virulence and resistance for some medically important multidrug-resistant (MDR) pathogens. This will help the future scientists to clearly focus on some specific proteins to be targeted by against the available class of drugs and/or antibiotics with the broader perspective to develop novel antimicrobial agents.